THE AWARENESS OF STUDENTS AT THE UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES, VIETNAM NATIONAL UNIVERSITY TOWARDS INTERCULTURAL COMMUNICATIVE COMPETENCE - Dieu Linh, Dao Thi; Quynh, Do Nhu (VNU Journal of Foreign Studies; Vol 35 No 5, 2019)
In today’s globalized world, a foreign language learner needs to not only master the four basic language skills, but also enhance their intercultural communication competence if he/she really wants to become a successful communicator. As a respond to this situation, intercultural communication has become an important content in foreign language teaching and learning. Using Bryam's intercultural communication competence model in 1997, the researchers aim at investigating the awareness of students from the University of Languages and International Studies ​​- Vietnam National University Hanoi towards intercultural communication competence, namely its definition, its significance, as well as their evaluation of current teaching and learning practices. Through a questionnaire survey of 458 students, the findings show a growing awareness of students to this competence, yet an unsufficient training in language classroom as well as a lack of self-consolidation outside class. More multicultural extra-curricular activities and culture-interrelating activities in language classroom are what we suggest to better develop this competence.